[4]Helicene-based anions in electrocrystallization with tetrachalcogeno-fulvalene donors. Issue 10 (23rd February 2022) - Zigon, Nicolas; Avarvari, Narcis
Abstract : Electrocrystallization of TMTTF, TMTSF and BEDT-TTF donors with the first helicene sulfonate-based anions provided crystalline radical cation salts with various donor : anion stoichiometries and packing patterns. Abstract : Electrocrystallization is a ubiquitous tool for the assembly of ions formed in situ from electroactive precursors into ordered crystalline macroscopic assemblies. Using tetrachalcogeno-fulvalene derivatives, many conducting and superconducting materials have been developed over the past fifty years, generally referred to as organic molecular conductors. The introduction of chirality in the structure of such molecular materials is encouraged by the possible observation of exotic physical effects, such as electrical magneto-chiral anisotropy (eMChA). Chirality is more commonly caused by the organic electron donor rather than the inorganic counter-anion. Herein, the synthesis of organic electrolytes based on a [4]helicene scaffold is described. Tetrabutylammonium salts of [4]helicene carboxylate and sulfonate have been synthesized and characterized. Electrocrystallization with three organic donors, namely tetramethyl-TTF (TMTTF), bis(ethylenedithio)-TTF (BEDT-TTF) and tetramethyl-tetraselenafulvalene (TMTSF), provided crystals whose single-crystal X-ray analysis is reported. While a covalent adduct of TMTTF has been observed with the carboxylate salt as the electrolyte, the structures display either discrete organic donor stacks of TMTTF and TMTSF or chains of laterally connected dimers of BEDT-TTF when sulfonate salts are used.